2008
DOI: 10.1093/brain/awn307
|View full text |Cite
|
Sign up to set email alerts
|

PACAP38 induces migraine-like attacks in patients with migraine without aura

Abstract: Experimental studies have shown that infusion of vasoactive neurotransmitters may trigger headache or migraine-like attacks in man. Pituitary adenylate cyclase activating peptide-38 (PACAP38) is a strong vasodilator found in trigeminal sensory and parasympathetic perivascular nerve fibers. We therefore hypothesized that infusion of PACAP38 would cause headache in healthy subjects and migraine-like attacks in migraine patients. Twelve healthy subjects and 12 migraine patients were examined in two separate studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
434
4
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 384 publications
(470 citation statements)
references
References 50 publications
30
434
4
2
Order By: Relevance
“…Nonetheless, the ability of PACAP-38 to induce migraine, in contrast to VIP, strongly points to PAC 1 receptor activation as a possible mediator of migraine. Experimental data noted in this review suggest that vasodilatation, 10,33,35,36 mast cell degranulation, 44,62 and neurogenic inflammation 62 are induced by the VPAC receptors and therefore do not seem important in PACAP-38-induced migraine. Instead, PACAP-38 might modulate the PAC 1 receptors at the second-order trigeminal neurons.…”
Section: How Might Pacap-38 Induce Migraine?mentioning
confidence: 85%
See 1 more Smart Citation
“…Nonetheless, the ability of PACAP-38 to induce migraine, in contrast to VIP, strongly points to PAC 1 receptor activation as a possible mediator of migraine. Experimental data noted in this review suggest that vasodilatation, 10,33,35,36 mast cell degranulation, 44,62 and neurogenic inflammation 62 are induced by the VPAC receptors and therefore do not seem important in PACAP-38-induced migraine. Instead, PACAP-38 might modulate the PAC 1 receptors at the second-order trigeminal neurons.…”
Section: How Might Pacap-38 Induce Migraine?mentioning
confidence: 85%
“…Recent studies point to the involvement of PACAP in migraine pain. 10 Here we review the evidence on how PACAP might be implicated in specific receptor activation during migraine attacks and discuss how the PAC 1 receptor could be a novel target for migraine treatment.…”
Section: Introductionmentioning
confidence: 99%
“…A clinical study has revealed that intravenously administered PACAP-38 induces headache in healthy volunteers and migraine-like attacks in patients with migraine without aura (6 h on average after the start of the infusion) [27], similarly to the effect of NTG in causing headache [74,75]. Moreover, the decrease of the mean blood flow velocity in the middle cerebral artery and the increase of the diameter of the superficial temporal artery were also observed in the PACAP study of the migraineurs.…”
Section: Pacap -Neuropeptides Nociception Trigeminal System Migrainementioning
confidence: 83%
“…Among the numerous "migraine-related" processes and substances, recent studies have potentially implicated the vasoactive PACAP in the pathophysiology, and hence in the future therapy of migraine [27,28].…”
Section: Therapymentioning
confidence: 99%
See 1 more Smart Citation